ENHANCING STUDENTS' INTEREST IN LEARNING MATHEMATICS THROUGH THE IMPLEMENTATION OF PROBLEM-BASED LEARNING: A CLASSROOM ACTION RESEARCH - Rahayu, Sri Mulya; Afisah (CV. Doki Course and Training, 2025)
This classroom action research aims to enhance students' interest in learning mathematics through the implementation of the Problem-Based Learning (PBL) model in Class X.6 at SMA PGRI 2 Palembang during the 2024/2025 academic year. The study was conducted in two cycles, each consisting of planning, action, observation, and reflection. The participants comprised 37 students. Data collection involved interviews, observations, questionnaires, field notes, and documentation. The average observation score for student interest increased from 65.28% in the first cycle to 78.73% in the second. Questionnaire data showed a rise from 82.32% to 86.81%. These results indicate that PBL effectively improves students' interest in learning mathematics.